2021
DOI: 10.33369/joall.v6i1.11800
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical Moves and Linguistic Realizations of Research Article Abstracts by Indonesian Authors in Applied Linguistics Published in International Journals

Abstract: The existence of abstract is compulsory within a research article (RA). Abstract is a summary or brief overview that describes entire content of RA. At a glimpse, abstract tells readers what the RA is all about and at the same time, it acknowledges readers and allows them indirectly to give pre-assessment about quality of the RA. This study aims to find rhetorical moves and linguistic features; tenses and voice forms of RA abstracts by Indonesian authors in Applied Linguistics published in international journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…As an answer to the main issue of rhetorical moves, this research will work on the assumption that Hyland's (2000), Bhatia's (1993), andSwales' (1990) move models are mostly used in RAs abstracts, moves occurrence are categorized as obligatory moves and supplementary moves, and linguistic features (for example : Andika, et al, 2018;Amnuai, 2019;Balagtas & Domingo, 2021;Can, et al, 2016;El-Dakhs, 2018;Fauzan, et al, 2020;Kurniawan & Sabila, 2021;Husnul, et al, 2021;Shamsabadi, et al, 2014;Pratiwi & Kurniawan, 2021).…”
Section: The Tendency Of Rhetorical Movementioning
confidence: 99%
See 4 more Smart Citations
“…As an answer to the main issue of rhetorical moves, this research will work on the assumption that Hyland's (2000), Bhatia's (1993), andSwales' (1990) move models are mostly used in RAs abstracts, moves occurrence are categorized as obligatory moves and supplementary moves, and linguistic features (for example : Andika, et al, 2018;Amnuai, 2019;Balagtas & Domingo, 2021;Can, et al, 2016;El-Dakhs, 2018;Fauzan, et al, 2020;Kurniawan & Sabila, 2021;Husnul, et al, 2021;Shamsabadi, et al, 2014;Pratiwi & Kurniawan, 2021).…”
Section: The Tendency Of Rhetorical Movementioning
confidence: 99%
“…Both Amnuai (2019) and Husnul et al (2021) analyzed sixty RA abstracts following Hyland's (2005) five-move model and considered the move category. Husnul et al (2021) found that Purpose, Method, and Product moves exist in the abstracts and are categorized as obligatory.…”
Section: The Tendency Of Rhetorical Movementioning
confidence: 99%
See 3 more Smart Citations